Islam. (1988)
Part 1 covers the history, basic beliefs, and important rituals of Islam. Part 2 shows how the religion is adapting to the modern world and outlines some of the schisms within the faith.
With teacher's guide and spirit masters.
Keywords: Islam; Religions of the world